2018
DOI: 10.3126/jnhrc.v15i3.18841
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Intravenous Ferric Carboxy Maltose in Iron Deficiency Anaemia During Postpartum Period

Abstract: Background: Iron deficiency is the commonest treatable cause of postpartum anaemia. Parenteral iron therapy results in faster and higher replenishment of iron stores and correction of haemoglobin levels with better compliance. Ferric Carboxy Maltose is an effective and a safe option which can be administered intravenously in single total correction dose without any serious adverse effects.The study was done to evaluate the efficacy and safety of Ferric Carboxy Maltose in the treatment of iron deficiency anaemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…(8) Misra et al had reported that mean haemoglobin levels had significantly increased over a period of three weeks after Ferric Carboxymaltose administration. (5) Naqash A et al had reported from Jammu and Kashmir a significant increase in the mean Hb was observed from 7.76 ± 0.709 to 13.25 ± 0.606 in patients treated with FCM and 7.64 ± 0.710 to 11.59 ± 0.733 g/dL (p < 0.001) in patients treated with IS after four weeks of therapy. (6) In our study, only 2 patients were pregnant.…”
Section: Baselinementioning
confidence: 89%
See 1 more Smart Citation
“…(8) Misra et al had reported that mean haemoglobin levels had significantly increased over a period of three weeks after Ferric Carboxymaltose administration. (5) Naqash A et al had reported from Jammu and Kashmir a significant increase in the mean Hb was observed from 7.76 ± 0.709 to 13.25 ± 0.606 in patients treated with FCM and 7.64 ± 0.710 to 11.59 ± 0.733 g/dL (p < 0.001) in patients treated with IS after four weeks of therapy. (6) In our study, only 2 patients were pregnant.…”
Section: Baselinementioning
confidence: 89%
“…They concluded that intravenous Ferric Carboxymaltose was an effective and a safe treatment option for iron deficiency anaemia and has an advantage of single administration of high doses without serious adverse effects. (5) Naqash A et al had reported from Jammu and Kashmir about 200 patients at Department of Obstetrics and Gynaecology, Sher-I-Kashmir Institute of Medical Sciences Medical College and Hospital, Jammu and Kashmir, India identified with IDA. Intravenous FCM and Iron Sucrose (IS) were both given as per the protocol.…”
Section: Baselinementioning
confidence: 99%
“…Yet, there is no consensus on whether this should be a first‐line option for moderate or severe cases of anemia. If Hb < 90–95 g/L, IV iron therapy may be a better option than oral iron 42 as the former increases iron deposits more rapidly and achieves a higher Hb level at 6 weeks postpartum (Mishra) 43,44 . Recent studies show the advantages of using IV ferric carboxymaltose.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show the advantages of using IV ferric carboxymaltose. It is effective, well‐tolerated, and is not associated with serious adverse effects in the postpartum period 44 . Administration of high doses of iron in a single infusion reduces the cost of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…As their examination was too little they didn't have a lot of contrasts in unfriendly impacts. (Mishra et al, 2015) mean absolute iron shortage was around 1000 mg against which mean genuine basic iron managed through FCM infusion/imbuement was likewise 1000mg speaking to 100% recharging of shortfall. Treatment with FCM expanded mean Hb by 2.37 gm/d in all patients which is measurably huge.…”
Section: Discussionmentioning
confidence: 99%